A Comparison of Two Monoterpenoid Synthases Reveals Molecular Mechanisms Associated With the Difference of Bioactive Monoterpenoids Between Amomum villosum and Amomum longiligulare - Zhao, Haiying; Li, Meng; Zhao, Yuanyuan; Lin, Xiaojing; Liang, Huilin; Wei, Jieshu; Wei, Wuke; Ma, Dongming; Zhou, Zhongyu; Yang, Jinfen (Frontiers in Plant Science, 2021)
The fruits of Amomum villosum and Amomum longiligulare are both used medicinally as Fructus Amomi the famous traditional Chinese medicine, however, the medicinal quality of A. villosum is better than that of A. longiligulare. Volatile terpenoids in the seeds, especially bornyl acetate and borneol, are the medicinal components of Fructus Amomi. The volatile terpenoids and transcriptome of developing seeds of A. villosum and A. longiligulare were compared in this study. The result revealed that the bornyl acetate and borneol contents were higher in A. villosum than in A. longiligulare. Additionally, six terpenoid synthase genes (AlTPS1–AlTPS6) were screened from the transcriptome of A. longiligulare, and AlTPS2 and AlTPS3 were found to share 98% and 83% identity with AvTPS2 and AvBPPS (bornyl diphosphate synthase) from A. villosum, respectively. BPPS is the key enzyme for the biosynthesis of borneol and bornyl acetate. Biochemical assays improved that AlTPS2 had an identical function to AvTPS2 as linalool synthase; however, AlTPS3 produced camphene as the major product and bornyl diphosphate (BPP) as the secondary product, whereas AvBPPS produced BPP as its major product. There was only one different amino acid between AlTPS3 (A496) and AvBPPS (G495) in their conserved motifs, and the site-directed mutation of A496G in DTE motif of AlTPS3 changed the major product from camphene to BPP. Molecular docking suggests that A496G mutation narrows the camphene-binding pocket and decreases the BPP-binding energy, thus increases the product BPP selectivity of enzyme. In addition, the expression level of AvBPPS was significantly higher than that of AlTPS3 in seeds, which was consistent with the related-metabolites contents. This study provides insight into the TPS-related molecular bases for the biosynthesis and accumulation differences of the bioactive terpenoids between A. villosum and A. longiligulare. BPPS, the key gene involved in the biosynthesis of the active compound, was identified as a target gene that could be applied for the quality-related identification and breeding of Fructus Amomi.